2020
DOI: 10.1002/cbdv.202000103
|View full text |Cite
|
Sign up to set email alerts
|

Caesalpanins A–C, Three Dimeric Cassane Diterpenoids from the Seeds of Caesalpinia sappan L.

Abstract: Three dimeric cassane diterpenoids, caesalpanins A-C, were isolated from the seeds of Caesalpinia sappan L., as well as three known compounds. Their structures were determined via analysis of 1D-, 2D-NMR, and HR-ESI-MS data. Caesalpanins A and B were the second and third compounds that presented a nitrogen-containing cassane diterpenoid dimer linked through one ether bond between C-19 and C-20'. Caesalpanin B exhibited moderate cytotoxic activity against MCF-7 cell lines with IC 50 value of 29.98 μM. Caesalpan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The Nitric oxide (NO) production inhibition of the compounds ( 1 ) was determined using a procedure described before [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Nitric oxide (NO) production inhibition of the compounds ( 1 ) was determined using a procedure described before [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…as aromatic compounds (9), homoisoflavonoids (10) phenolic compounds (11), protosappanins (12) and diterpenoids (13). Biological studies such as anticancer (14), antibacterial (15), analgesic (16), immunomodulatory (17) antioxidant, anthelmintic properties (18) and toxicological studies (19) have been already documented.…”
Section: Research Articlementioning
confidence: 99%
“…The latter two compounds do not show significant inhibitory activity against nitric oxide ( Zhao et al, 2014 ), a vasodilator found in blood vessels. The seeds of C. sappan are rich in diterpenoids, including caesalsappanin A−N, R and S ( Ma et al, 2015 ; Bao et al, 2016 ; Zhu et al, 2017 ; Wang et al, 2020 ); phanginin A−K and R‒T ( Yodsaoue et al, 2008 ; Bao et al, 2016 ); and ester glycosides, namely caesateroside A−C ( Wang et al, 2020 ). Oleanolic acid, a triterpenoid, has also been isolated from the plant ( Zheng et al, 2020 ).…”
Section: Caesalpinia Sappan and Its Bioactive Metabolitesmentioning
confidence: 99%